ANALISIS SISTEM INFORMASI MANAJEMEN BARANG MILIK DAERAH (SIMDA-BMD) PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN PEGUNUNGAN BINTANG - Fesa Asy Syifa Nurul Haq; Novi Trihadi; Helda Ariska; Vani Avrilia Puspitaningrum (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2021)
The financial SIMDA application which is an application of information system technology used for integrated regional financial management also serves as a control tool for various activities that occur in each Regional Device Organization (OPD). To support inventory, the evaluation of the regional property management information system (SIMDABMD) is considered necessary with the aim is to find out whether the SIMDA-BMD information system that runs has been effective and efficient in supporting asset inventory in Gunung Bintang Regency. This type of research is descriptive research with samples using a purposive samplingapproach. The sample in this study was the bpkad asset staff of Bintang Mountains. SIMDA-BMD application implemented by the Government of Gunung Bintang Regency as a computer-based application that is integrated is quite good in helping the government manage regional property